The infinite woman - Carmignac, Charles; Robinne, Grégoire (Éditions Dilecta, 2024)
"Strong, lustful, fatal, loving, demonic, tempting or mythical, women have been represented in many ways over the centuries, often in response to a patriarchal vision of the world. Exploring identity, sexuality, pleasure and power, The lnfinite Woman sheds light on the ways in which women have been viewed from the earliest myths to the most contemporary and subversive representations. Here, art liberates women's bodies from Western beauty canons, offering reinvented models that challenge not only social norms, but also the limits of art itself as well as its oppressive categories." -- Gallery website
Impressum: "The Infinite Woman", du 27 avril au 3 novembre 2024
Text französisch
Keywords: Geschichte 1960-2024; Künstlerin; Frau -- Motiv; Kunst; Ausstellungskatalog -- Fondation Carmignac -- 27.04.2024-03.11.2024 -- Hyères